2011
DOI: 10.1063/1.3628315
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/GaN Schottky diodes: Stability at elevated temperatures

Abstract: Rectification and thermal stability of diodes formed at graphene/GaN interfaces have been investigated using Raman Spectroscopy and temperature-dependent current-voltage measurements. The Schottky barriers formed between GaN and mechanically transferred graphene display rectification that is preserved up to 550 K with the diodes eventually becoming non-rectifying above 650 K. Upon cooling, the diodes show excellent recovery with improved rectification. We attribute these effects to the thermal stability of gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
72
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 19 publications
6
72
3
Order By: Relevance
“…Furthermore, the experimentally obtained  B value of 0.74 eV [33,34] was even larger than the predicted value. These inconsistent results indicate that, for the successful development of graphene integrated GaN-based semiconductor devices, the electrical characteristics and carrier transport mechanism of the graphene-GaN contact should be thoroughly investigated.…”
Section: Introductioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Furthermore, the experimentally obtained  B value of 0.74 eV [33,34] was even larger than the predicted value. These inconsistent results indicate that, for the successful development of graphene integrated GaN-based semiconductor devices, the electrical characteristics and carrier transport mechanism of the graphene-GaN contact should be thoroughly investigated.…”
Section: Introductioncontrasting
confidence: 65%
“…On the one hand, thermally stable rectifying behavior was also observed for the graphene contacts formed on n-type GaN by Tongay et al [33,34], suggesting that the graphene on n-GaN be a promising candidate for the Schottky rectifiers. This finding is strange considering that the  B expected to form at the graphene/n-GaN interface is as low as ~0.4 eV due to the small work function difference between graphene and n-GaN, implying that the graphene contact to n-GaN should produce poor rectifying behavior.…”
Section: Introductionmentioning
confidence: 78%
“…Typically, ideality constants greater than the unity imply a number of possibilities: (1) additional charge transport processes such as thermionic field emission exist at the interface, 17 (2) the SBH is bias dependent since the graphene Fermi level is bias dependent, [17][18][19] (3) the image force lowering 16 effect is significant at the interface, and/or (4) Schottky barrier inhomogeneity is present in the junction area. 20 In accord with these possibilities we suggest that for pristine graphene/nSi, ideality constants greater than unity can be associated with the existence of charge puddles on the graphene that are unintentionally formed during the graphene processing steps and which give rise to associated Schottky barrier inhomogeneities.…”
Section: Introductionmentioning
confidence: 99%
“…Unusual properties of graphene promising for a variety of novel applications [23][24][25][26][27][28] have also triggered significant interest in one or several atom-thick honeycomb structures of binary compounds. Early experimental studies aiming to synthesize and characterize novel monolayer materials have revealed that graphene-like sheets of BN are also stable.…”
Section: Introductionmentioning
confidence: 99%